Protective immune responses in bovine theileriosis - Morrison, W. Ivan; Emery, D.L.; Teale, A.J.; Goddeeris, Bruno M. (Cambridge University Press, 1986)
The protozoan parasite Theileria parva is the causal agent of an acute, usually fatal, disease of cattle characterized by widespread parasitism and destruction of cells of the lymphoid system. Animals which recover from infection are immune to challenge with the homologous stock of the parasite. Furthermore, immunity can be induced by various infection and treatment regimes. There are two potential levels at which protective immunity may operate, namely the sporozoite and the macroschrizont-infected cell. It has been shown that serum from immune cattle and anti-sporozoite monoclonal antibodies can neutralize sporozoite infectivity. However, it is still not clear whether such antibodies are sufficiently efficiently efficient in vitro to prevent infection. Methods of immunization currently in use appear to depend on the establishment of active infection and Development of the parasite to the macroschizont stage in recipient cattle. However, three out of four cattle have been successfully immunized with a cell membrane fraction prepared from autologous Theileria-infected cell lines. During immunization by infection and treatment or following challenge of immune cattle, cell-mediated cytotoxic responses are generated against macroschizont-infected cells. The activity of these cells is restricted by class I major histocompatibility (MHC) antigens, and their appearance shows a close correlation with the Development of immunity. These findings suggest that the parasite induces antigenic changes on the surface of infected host cells and that cell-mediated immune responses against cell-surface antigens are important in the acquisition of protective immunity.